Review of the Literature on the Impact of Mergers on Innovation - Norbert Schulz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
Both M&A and innovation are instruments for growth and competitive advantage. Therefore they are fundamental to each firm?s competitive strategy. Usually, both instruments have been studied separately, but much less in conjunction. This is unfortunate as both processes - the process of innovation and the process of mergers and acquisitions - are intimately connected. The impact of mergers on innovation can only be rigorously assessed, if the converse direction of influence - mergers caused by innovation - is accounted for. Therefore this review tries to take a balanced view on both processes and to point out links between them. Nevertheless, the focus is on the impact of mergers on innovation. This discussion paper is identical with an older version with the title ?Review on the Literature of Mergers on Innovation?.
Keywords: O31; L25; L10; 330; innovation incentives; market structure; merger incentives; Fusion; Übernahme; Innovation; Immaterialgüterrechte; Wettbewerb; Welt